A NuSTAR Study of Quasiperiodic Oscillations from the Ultraluminous X-Ray Sources in M82 - Hamza El Byad; Matteo Bachetti; Silvia Columbu; Giuseppe Rodriguez; Maura Pilia; Matthew J. Middleton; Dominic J. Walton; Murray Brightman; Hannah Earnshaw; Karl Forster; Brian Grefenstette; Felix Fürst; et al. (The Astrophysical Journal)
The study of quasiperiodic oscillations (QPOs) in X-ray binaries provides valuable insights into the physics of accretion around compact objects. The M82 galaxy hosts multiple ultraluminous X-ray sources, including two prominent ones—X-1 and X-2—where X-1 is suspected to harbor an intermediate-mass black hole. In this work, we analyze data from 39 NuSTAR observations acquired between 2014 and 2024 to investigate the aperiodic X-ray variability in M82. In particular, we study in detail the evolution of the QPOs from M82 X-1 in the range 20–300 mHz. We do not find additional timing features in the data, besides a frequently present broad noise component at lower frequencies. The QPO behaves similarly to other classes of low-frequency oscillations in accreting compact objects, both black holes and neutron stars.